Women and Violence The Agency of Victims and Perpetrators - Marway, Herjeet; Marway, Herjeet; Widdows, Heather (Basingstoke Springer Nature Palgrave Macmillan [Imprint], 2015)
This edited collection explores the agency of women who do violence and have violence done to them. Topics covered include rape, pornography, prostitution, suicide bombing and domestic violence. The volume contributes to the philosophical and theoretical debate, as well as offering practical, social and political responses to the issues examined.
eng
Keywords: Ethics; Philosophy (General); Social sciences (General); Sociology (General); Women. Feminism; Morale; Crime and criminology; Crime and criminology; ethics (philosophy); Ethics and moral philosophy; Ethics and moral philosophy; Ethics; Feminism and feminist theory; Feminism and feminist theory; Gender studies, gender groups; Gender studies, gender groups; Gender studies: women and girls; Humanities; Philosophy and Religion; Philosophy; Philosophy; Social and political philosophy; Social and political philosophy; Social groups, communities and identities; Social groups; Social issues and processes; Social services and welfare, criminology; Social services and welfare, criminology; Society and culture: general; Society and culture: general; Society and social sciences Society and social sciences; Society and Social Sciences; Sociology and anthropology; Sociology and anthropology; Sociology; Sociology; Topics in philosophy; domestic violence; pornography; prostitution; rape; suicide bombing; violence; women